Analisis Potensi Ekonomi Dalam Menetapkan Rencana Pembangunan Kabupaten Kediri Ditengah Pandemi Covid-19 - Harianto, Kukuh (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2021)
The purpose of this study was to determine the superior and potential economic sector in the economy of Kediri Regency for the present and the future. The data used in this study is the Gross Regional Domestic Product at Current Prices (GRDP-CP) for five years. The analytical methods used in this research are Static Location Quotien (SLQ), Dynamic Location Quotien (DLQ), and Overlay Analysis. The results of the study show that there are 8 sectors that are included in the superior category, and there is 1 sector that is included in the superior and potential sector category, namely the communication and information sector. The communication and information sector is the basis sector for the present and the future. The results of the analysis show that the information and communication sector is the first development priority sector in development & has a more dominant growth compared to other sectors and is a sector that has a comparative advantage.